PERANAN GAME EDUKASI PADA MODEL PEMBELAJARAN HYBRID LEARNING TERHADAP HASIL BELAJAR PAI SISWA KELAS VII DI SMP NEGERI 1 KOTA BOGOR - Sulistiyanti, Nur Afiyah; Mubarok, Zahid; Nawawi, Muhammad Kholil (FIKRAH, 2023)
Educational games are a form of creativity that teachers must have a during like pandemic today. The prolonged pandemic period makes the learning process unable to run normally as usual. Along with the times and technological advances, learning models are created that are able to support learning in order to adapt to the pandemic so that learning can tun smoothlyand have a good impact on student learning an outcomes in PAI subjects. The purpose of this study was to describe the implementation educational games in the hybrid learning model, to find out the supporting factors causing the lack of interest in PAI subjects, and the role of educational in PAI learning outcomes. The research method is qualitative with a case study approach, this research wa carried out at SMP Negeri 1 Bogor City for seventh grade students. The primary data sources in this study were PAI teacher and seventh grade students. Data collection techniques observation, interviews, and documentation were than validated by triangulation of sources. Data analysis through the stages of data collection, data reduction and drawing conclusions. The result of this study state that educational games have many roles in the hybrid learning model, one of which is to improve students PAI learning outcomes. This is evidenced by the learning outcomes of PAI students increase and achieve completeness.